An overview on organic agriculture of Romania in the context of the current European development model - Steliana Rodino; Alina Butu; Marian Butu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 7th Edition of the International Symposium, November 2016, Bucharest, 2016)
This works stand as an overview on organic agriculture of Romania in the context of the current European development model, presenting relevant information on the organic sector, legislation in force and some data regarding the trade market, at national and European Level. Organic agriculture is a holistic system of production designed to maximize productivity of diverse communities within the agro-system, combining tradition, innovation and science to benefit the shared environment and promote fair relationships and a good quality of life for all involved. The organic production sector is one of the most dynamic industrial sectors of EU, with significant increase every year for the last 10 years, in response to the growth in consumers demand. According to official numbers, the ecological agriculture in Romania has seen an upward trend in recent years, both in the vegetable and livestock production sector. Although ecological agriculture represents narrow segments in terms of both acreage and production, it is gaining increased attention due to its sustainable principles of ecological importance and to the economic opportunities it may offer.
Keywords: N40; N50; Q01; Q15; 330; ecological agriculture; organic production; consumers awareness; natural balance